FASHION AND LIFESTYLE TRENDS ON THE PURCHASE OF MUSLIM WOMEN'S CLOTHING WITH RELIGIOSITY AS AN INTERVENTION VARIABLE - Ahmad Muqorobin; Adinda Muftiviany Nur Jamilah; Inna Putri Istiqomah; Alawiye Habeebulah Olawale; Bello Sani Yahuza (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2025)
The Muslim population in Yogyakarta has a percentage of 92.2%, sharia products will be in great demand, including Muslim fashion products. However, teenagers prioritize their style of dress and lifestyle rather than sharia restrictions in buying Muslim clothing. The purpose of the study was to determine the role of religiosity in making decisions to buy Muslim clothing for Muslim adolescent women with an age range of 17-24 years. This research is quantitative descriptive with multiple linear regression method with path analysis processed with SPSS. The sample in this study used quota sampling with 97 respondents. This study shows that fashion trends have an effect on purchasing decisions of 87.7%. Lifestyle variables have an influence on purchasing decisions of 29.9%. The religiosity variable had a relatively small influence on purchase decisions of 23.3%. Meanwhile, the influence of fashion trends on purchasing decisions through religiosity was 0.877<0.925 and the influence of lifestyle was 0.299<0.409.